End aid now: a prospect of financial synergies for a long-term Euro-Mediterranean cooperation on science, technology and innovation - Semeraro M.; Giannelli M.; Bogliotti C.; El-Zoheiry A.H.; Lacirignola C. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
The Mediterranean region has traditionally been an area of interest for the EU external relations. Several cooperation initiatives have been focussed on this region, within the framework of a “Mediterranean dimension” encompassing security, economic, social and political aspects. In 1995, the Barcelona Conference reinforced this framework in order to create a “shared peace, prosperity and security” area. This ambitious goal, re-launched by the creation of the Union for the Mediterranean (UfM), has not been fully achieved yet. With particular reference to Science, Technology and Innovation (STI), the EU cooperation policies with the Mediterranean Partner Countries (MPCs), supported by different co-funding tools, have not completely defined a harmonized institutional and regulatory co-ownership framework at multi-lateral level. This partial failure is mainly due to a poor governance of STI Euro-Mediterranean cooperation, and to the political scenario that has characterized the area in the past 20 years. The objective of this paper is to give food for thought on the rethinking of Euro-Mediterranean STI cooperation policies and tools by proposing a new governance that might ensure the sustainability of such cooperation. Considering the current political, social and economic conditions of the Mediterranean region, the first section of the paper describes the background of Euro-Mediterranean STI cooperation. In the second part emphasis is laid on stocktaking and critical assessment of co-financing instruments such as ERA-NET, ERA-NET plus and Article 185 of the Treaty on the Functioning of the EU, in order to identify their strengths and weaknesses. The third section highlights the need to renew the EU STI cooperation policy in the Mediterranean region on the basis of co-ownership and co-funding principles, through shared actions able to support co-development.